2010
DOI: 10.1029/2010jb007565
|View full text |Cite
|
Sign up to set email alerts
|

Slip distribution of the 2007 Bengkulu earthquake inferred from tsunami waveforms and InSAR data

Abstract: Joint inversion study using tsunami waveforms and InSAR data provides a new way to understand the magnitude and spatial extent of subduction zone earthquakes. A great earthquake (Mw 8.5) occurred on 12 September 2007 off the west coast of Bengkulu, Indonesia. The tsunami generated by the event was recorded by tide gauge stations around the Indian Ocean and by two bottom‐pressure sensors in the deep sea. The ground surface displacements produced by the earthquake on Pagai Islands and on Sumatra Island were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…In 2007, the Bengkulu earthquake occurred along the Sunda trench. Slip distribution of the 2007 Bengkulu earthquake was estimated using tsunami waveform data and InSAR data (Gusman et al 2010), and showed that the 2007 earthquake ruptured a deep part of the subducting plate. Subsequently, in 2010, the Mentawai tsunami earthquake occurred.…”
Section: Subfault Numbermentioning
confidence: 99%
“…In 2007, the Bengkulu earthquake occurred along the Sunda trench. Slip distribution of the 2007 Bengkulu earthquake was estimated using tsunami waveform data and InSAR data (Gusman et al 2010), and showed that the 2007 earthquake ruptured a deep part of the subducting plate. Subsequently, in 2010, the Mentawai tsunami earthquake occurred.…”
Section: Subfault Numbermentioning
confidence: 99%
“…Without a smoothing constraint, the result of the tsunami waveform inversion might be bumpy and non-physical, especially for cases with high spatial resolution (Wu and Ho, 2011). In other studies on tsunami waveform inversion by Baba et al (2005) and Wu and Ho (2011), an equality constraint was imposed to maintain the smoothness of the inverted parameters to satisfy the long wave assumption, while by Saito et al (2010) and Gusman et al (2010) Figure 8. Scatter plots of each inversion method with respect to the waveforms of the target source at all gauges.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both the uniqueness and the stability of solutions are sometimes difficult to attain without appropriate treatments. The most frequently employed techniques to maintain a stable solution is to use a smoothing constraint (Gusman et al, 2010(Gusman et al, , 2013Saito et al, 2010). Other than that, Koike et al (2003) suggested reducing the unknown parameters using the wavelet base to guarantee the uniqueness of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…They include the 2005 M w 8.6 Nias earthquake (Briggs et al, 2006) and the 2007 M w 8.5 Bengkulu earthquake (Gusman et al, 2010). Ionospheric disturbances by these earthquakes were studied by Cahyadi and Heki (2013) using a GPS network in Sumatra.…”
Section: The Case Of the Great Sumatra-andaman Earthquakementioning
confidence: 99%